PERANAN GURU PAI DALAM PEMELIHARAAN KEBERSIHAN DAN KESEHATAN DI SDN 23 SUNGAI TARAB KABUPATEN TANAHDATAR SUMBAR - Asmendri Asmendri (Ta'dib, 2008)
In general this study was aimed at 1) identifying the roles played by  Islamic teaching (PAI) teachers as educators in integrating PAI instructional materials into health education, 2) detecting PAI teachers’ participation in carrying out health services, and 3) identifying PAI teachers’ roles as the supervisor of healthy school environment at SDN 23 Sungai Tarab. The findings show that the teachers were able to integrate PAI instructional materials into health programs conducted by the school. Such integration was especially carried out by means of topic on thaharah. In addition, the teachers took active participation in any health service program at the school. Though the percentage of their participation was not as significant as the classroom teachers, they kept participating in any school health programs carried out by the school.Kata Kunci: guru, pemeliharaan, kebersihan, kesehatan